Pemberdayaan Masyarakat Melalui Peningkatan Kapasitas Mitigasi Bencana di Desa Cimara Kecamatan Cibeureum Kabupaten Kuningan - Nina Herlina; Yayan Hendrayana; Ilham Adhya; Toto Supartono; Zillan Zalila; Bima Aria Indra Prahasta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2022)
The importance of the community to have disaster knowledge, community or community participation is the spearhead of activities to deal with floods and landslides based on the knowledge and abilities possessed by the community. As a result of the catastrophic floods, communities suffered incalculable damage such as loss of property, livestock and crops. Cimara Village is a village that borders the Gunung Tilu Forest, it is predicted that disasters will occur due to illegal logging and forest destruction which continues to increase every year. However, until now no efforts have been made by the village government. So the purpose of this activity is to increase knowledge about various handling problems related to environmental damage, mitigation and disaster management that often occur in Cimara Village. The method used is in the form of socialization/counseling on the material of environmental damage and disasters. Based on the results of this activity, participants are able to understand the impact of environmental damage, disaster mitigation and post-disaster can run smoothly and need further approaches so that they can open up participants' insight and mindset in understanding the environment.